2020
DOI: 10.1002/jqs.3195
|View full text |Cite
|
Sign up to set email alerts
|

Beach ridges of Dali Lake in Inner Mongolia reveal precipitation variation during the Holocene

Abstract: Variability in East Asian summer monsoon precipitation during the Holocene remains of debate. In this study, we use a closed lake with well‐dated lake beach ridges located on the margin of the East Asian summer monsoon, a region highly sensitive to monsoon precipitation changes, to obtain a temporal sequence of water volume in North China. The elevation of each beach ridge calibrated to the modern lake level was surveyed. Optically stimulated luminescence dating of undisturbed sediments of beach ridges was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Previous studies have shown that the sand field in northern China was dry and experienced widespread aeolian activity during the early Holocene, with considerable dune stabilisation and soil formation during the middle Holocene (Lu et al , 2005, 2013b; Mason et al , 2009). These findings are supported by the regional lake sediment records (Chen et al , 2015, 2020; Jiang et al , 2020; Xiao et al , 2004) but conflicted with speleothem records of the monsoon intensity during the Holocene (Cai et al , 2010; Wang et al , 2005). Thus, a multiproxy investigation of the loess–palaeosol sequence with a high sedimentation rate can be used to elucidate the relationship among monsoon precipitation, vegetation, aridity and soil formation, and may explain the debates from diverse palaeoclimatic and palaeoenvironmental archives.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Previous studies have shown that the sand field in northern China was dry and experienced widespread aeolian activity during the early Holocene, with considerable dune stabilisation and soil formation during the middle Holocene (Lu et al , 2005, 2013b; Mason et al , 2009). These findings are supported by the regional lake sediment records (Chen et al , 2015, 2020; Jiang et al , 2020; Xiao et al , 2004) but conflicted with speleothem records of the monsoon intensity during the Holocene (Cai et al , 2010; Wang et al , 2005). Thus, a multiproxy investigation of the loess–palaeosol sequence with a high sedimentation rate can be used to elucidate the relationship among monsoon precipitation, vegetation, aridity and soil formation, and may explain the debates from diverse palaeoclimatic and palaeoenvironmental archives.…”
Section: Introductionmentioning
confidence: 78%
“…As discussed above, δD wax can represent changes in monsoon rainfall amount in Yulin, which can also explain the change in ACL. Pollen records from lakes in the marginal monsoon regions, including Bayanchagan Lake (Jiang et al , 2006) and Daihai Lake (Xiao et al , 2004), as well as a recent lake shoreline study (Jiang et al , 2020), all show a decrease in the proportion of woody plants and monsoon rainfall since ~6 ka, which has been attributed to a decrease in humidity in this region (Wang and Feng, 2013). This decrease is also supported by simulation results for summer monsoon rainfall in this region (Liu et al , 2014).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This age resolution is unprecedented in other lakes in East Asia and provides a high-resolution history of this large and rapid drying. (Goldsmith et al, 2017;Jiang et al, 2020). (c) Lake Chagan (Li et al, 2020).…”
Section: Compiling Lake-level Data From Closed-basin Lakes At the Mon...mentioning
confidence: 99%
“…(Xiao et al, 2008;Xiao et al, 2009). However, reconstructed lake-level fluctuations based on the OSL dating of beach ridges of Dali Lake reflected the lower lake level related to the reduced monsoon precipitation from 12 to 7 ka and the high lake level with a maximum monsoon precipitation during 7-5 ka (Jiang et al, 2020). In addition, lakes in eastern Inner Mongolia also revealed the distinct timing of highstands.…”
Section: Introductionmentioning
confidence: 98%